Pengaruh Price Earning Ratio (PER), Net Interest Margin (NIM) dan Earning Per Share (EPS) Terhadap Harga Saham pada Bank BUMN yang Terdaftar di BEI - Tria Rosalina; Aliah Pratiwi; Aris Munandar (INDO PUBLISHING, 2025)
This study examines the effect of the Price to Earnings Ratio (PER), Net Interest Margin (NIM), and Earnings Per Share (EPS) on stock prices in state-owned banks listed on the Indonesia Stock Exchange (IDX). This associative study aims to determine the relationship between the two variables. This study examines the effect of the Price to Earnings Ratio (X1), Net Interest Margin (X2), and Earnings Per Share (X3) on bond stock prices (Y). The population of this study is financial report data from 47 state-owned banking companies listed on the IDX. The sample used is financial report data from four state-owned banking companies listed on the IDX: Bank BRI, Bank BNI, Bank MANDIRI, and Bank BTN, from 2020 to 2024 (5 years). The conclusions in this research are (a) Price Earning Ratio (PER) has no effect on stock prices (b) Net Interest Margin (NIM) has no effect on stock prices (c) Earning Per Share (EPS) has an effect on stock prices and (d) Price Earning Ratio (PER), Net Interest Margin (NIM) and Earning Per Share (EPS) have an effect on stock prices